2021
DOI: 10.1097/sla.0000000000005186
|View full text |Cite
|
Sign up to set email alerts
|

Incivility, Work Withdrawal, and Organizational Commitment Among US Surgeons

Abstract: Objective: To evaluate the prevalence of incivility among trainees and faculty in cardiothoracic surgery, general surgery, plastic surgery, and vascular surgery in the U.S, and to determine the association of incivility on job and work withdrawal and organizational commitment. Background: Workplace incivility has not been described in surgery and can negatively impact the well-being of individuals, teams, and organizations at-large. Methods: Using a cross-sectional, web-based survey study of trainees and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In this study, reports of incivility were in line with those reported in other institutions worldwide [3][4][5][6][7]. While the absolute frequency may appear small (i.e., incivility events were observed or experienced a few times a week on average per person), efforts to reduce incivility are warranted given the growing evidence that incivility has the potential to impede team coordination and impact safety and patient outcomes.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In this study, reports of incivility were in line with those reported in other institutions worldwide [3][4][5][6][7]. While the absolute frequency may appear small (i.e., incivility events were observed or experienced a few times a week on average per person), efforts to reduce incivility are warranted given the growing evidence that incivility has the potential to impede team coordination and impact safety and patient outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…Incivility can have significant costs to the well-being of staff and ultimately to patients, as well as having a negative impact on the overall culture, work performance, absenteeism and turnover, and commitment to the organization [ 5 ]. While research is beginning to address detrimental impacts of incivility, there is a paucity of work explicating mechanisms through which incivility can impact well-being outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations